(untitled) (Indian Journal of Child Health, 2019)
Background: Hepatitis is a major health problem in both developing and developed countries, with various infective and non-infective causes. Aim: This study aims to estimate the proportion of hepatitis A and E as a causative agent in children presenting with acute hepatitis and to study their clinical and biochemical parameters. Materials and Methods: The present study was conducted on all children attending or admitted with clinical features of acute hepatitis defined as hepatomegaly, fever >38°C, malaise, dark urine, and/or jaundice. All children included were clinically examined and relevant investigations were sent. All the data were entered in a structured pro forma and statistical analysis was done. Results: A total of 254 patients were studied. Hepatitis A virus (HAV) was the most common with 95.08% of cases and occurred in the age group of ?5 years. Hepatitis E virus (HEV) was more common in ?10 years age group and was observed in 13.11% of cases. Common prodromal symptoms in hepatitis patients were fever, anorexia, vomiting, and abdominal pain, observed in 82.5%, 32.5%, 55.5%, and 50.5% of cases, respectively, with no significant difference between HAV and HEV. In liver biochemistry, there was no significant difference in serum bilirubin, serum glutamic oxaloacetic transaminase, and serum glutamate pyruvate transaminase values between HAV and HEV. Conclusion: There are no significant differences in both enterically-transmitted hepatitis viruses and the only way to differentiate between them is by serological tests.